A inclusão de estudantes com deficiência no Ensino Superior : preconceito, diferença e exclusão na perspectiva dos coordenadores de curso da UFR - Nogueira, Camila Soncini (2022)
The process of democratizing education has enabled access for all people, regardless of their individual differences, to all levels and modalities of education. Even before legal initiatives by the public power, it is historically considered precisely as the struggle of social movements for the conquest and advancement of inclusive education. This legitimacy, induced by several fronts of struggle, fostered some initiatives of investment in education, which people with disabilities reach Higher Education. However, despite limits, inclusion still finds many. It is possible to observe that a reflection of education between inclusion, difference and prejudice constitutes a challenge for professionals, being one of the difficulties for, in fact, this process of inclusion of people with disabilities in Higher Education really. Therefore, we ask ourselves: considering that the academy is seen as an institution of knowledge and the professors are intermediaries, can there be prejudice and exclusion in the professors' speeches, especially in the discourses of the course coordinators, those processes in charge of to mediate the student's relationship with the institution, especially with regard to pedagogical issues? It is considered such narratives, since we seek to explore and understand the practices of the inclusion process carried out in higher education with students with disabilities. Taking these questions as basic questions, the general objective of this research was to understand the perception of undergraduate course coordinators about the inclusion and permanence of students with disabilities in Higher Education. This study has, as a methodological basis, empirical social research of a qualitative nature, in accordance with the proposal presented by the authors of critical theory. In this case, we analyze in this work the Statute that currently governs the researched higher education institution and the Institutional Development Plan (PDI), developed by the tutoring university, which consolidates all development actions. In addition, we applied a questionnaire composed of twenty-eight semi-structured questions, aimed at ten professors who act as coordinators of the undergraduate course at the University. This instrument allowed us to know some aspects of the condition of students with disabilities assisted by the institution, in addition to verifying signs of prejudice and exclusion. Therefore, this dissertation offers elements so that the academy can evaluate the way it deals with difference, as well as opportunities and invites the entire academic community to open up to daily changes in the face of numerous veiled and normalized prejudices.